The Online Advertising Tax as the Foundation of a Public Service Internet - Fuchs, Christian (CAMRI Policy Briefs, 2018)
"Online advertising will soon form the largest share of global advertisement revenues. Google and Facebook netted profits of US $29 billion in 2016. While these two giants control more than 66% of all online advertising revenues complex legal company structures have minimised their tax liabilities. This extended policy report considers where they should be taxed and where the value of their activities is actually created. It argues that tax paid by those platforms should be levied in the country where platform users are located when they click on or view an advertisement. Furthermore, the report examines the practical steps needed to ensure transparent accounting of taxed transactions in order to avoid long term negative effects for media and democracy. Considering counter-arguments the author makes the case for an online advertising tax alongside a public service Internet strategy that could support other viable platforms and counter the dangers of duopoly or oligopoly and the high risks of financial bubbles in a world where advertising is the Internet's dominant business model."